Spin-flip plus phonon raman scattering: A new second-order scattering process - Hollis, R; Ryan, J; Scott, J (1975)
A new second-order light scattering process has been observed which yields line spectra at frequency shifts LO±SF, where LO is a longitudinal optical-phonon frequency, and SF is an electron or hole spin-flip frequency. The scattering is highly resonant, and the proposed mechanism is analogous to that for multiple-phonon line spectra and double spin-flip scattering. © 1975 The American Physical Society.